How influencers motivate inactive adolescents to be more physically active: a mixed methods study - Aschwanden, Rahel; Messner, Claude (Frontiers in Public Health, 2024)
Introduction Regular physical activity offers numerous health benefits, particularly for adolescents. However, only 14% of school-aged children in Switzerland achieve the World Health Organization's recommendation of 60 min of moderate to vigorous physical activity per day. Changing health behaviors is a complex process in which understanding behavioral and communication patterns is crucial. Because adolescents spend substantial time on social media channels and obtain information from them, these are potential channels for accessing health-related content. This study explores the questions of which influencers and what content motivate adolescents to be more physically active and whether influencers can impact enjoyment and the intention to engage in physical activity. Methods The study employed a convergent mixed methods approach, combining self-assessment questionnaires and semi-structured interviews. Ninety-three adolescents aged 14–20 years who exercised < 1 h per day participated. They followed one of the six participating influencers on Instagram. Over 6 weeks, the questionnaires collected quantitative data, measuring enjoyment, stages of change, and physical activity levels. Furthermore, semi-structured interviews were conducted with 23 adolescents and six influencers to gain in-depth insights. Results The quantitative findings indicate that adolescent followers enjoyed physical activity more after the social media intervention and at follow-up than at the beginning of the study. The followers' stages of change progressed over time. Compared with those following more athletic influencers, followers of nonathletic influencers (that is, a singer, a journalist, and an eFootballer) showed increased physical activity over time. Qualitative analysis highlighted Instagram factors influencing physical activity, including resonance with influencers' lifestyles and preference for simple, relatable activities. Authentic content was positively associated with increased exercise, particularly among already motivated followers. Discussion Unexpectedly, nonathletic influencers, such as a singer, a journalist, and an eFootballer, motivated adolescents best despite their nontraditional focus on physical activity. Their success stems from relatable lifestyles and simple activities that are easily incorporated into their daily routines. Conversely, athletic influencers demonstrated challenging exercises that were fascinating but difficult to adopt. This finding suggests the potential for utilizing nonathletic influencers in future campaigns targeting inactive adolescents.